Inibidor de urease (NBPT) e a eficiência da ureia aplicada em dose única ou parcelada na cultura do sorgo sacarino - Santana, Cesar Augusto (Universidade Federal de São Carlos, 2018)
Sweet sorghum has been considered an agricultural crop with great potential for the production of bioenergy, recommended for cultivation in sugarcane reform areas to supply raw material for the production of ethanol in the off-season of sugarcane in Brazil. Depending on the bioethanol production system, the entire sweet sorghum plant is harvested, with large exports of nutrients from the agricultural area. Although there is little information in the literature on more specific fertilizer management for sweet sorghum, nitrogen fertilization with 20-40 kg ha-1 of N at sowing and 60-120 kg ha-1 of N in topdressing fertilization is currently recommended. The volatilization of N from urea, the nitrogen fertilizer most used in Brazilian agriculture, is one of the main routes of N loss and one of the main reasons for the low efficiency of nitrogen fertilizers. One of the recommended practices for reducing N losses through volatilization is the incorporation of urea into the soil. Due to the practical difficulty and costs of this operation, some innovative technologies have the possibility of producing stabilized fertilizers, including urea with the additive N- (n-butyl) thiophosphoric triamide (NBPT), a urease-inhibiting substance that slows down the rate of urea hydrolysis and reduces N losses through volatilization. The objective of the work was to evaluate the agronomic performance of sweet sorghum fertilized with common urea and with urea with urease inhibitor NBPT for the supply of the recommended N in full dose at sowing or in split doses at sowing and topdressing fertilizations. The experimental design consisted of four randomized blocks, consisting of six treatments: T1 - control (without fertilization); T2 - control (without nitrogen fertilization); T3 - common urea applied at planting; T4 - common urea applied in split application (planting and topdressing); T5 - urea with urease-NBPT inhibitor applied at planting; T6 - urea with urease-NBPT inhibitor applied in split application (planting and topdressing). The plant height, stalk production, dry and fresh matter, panicle mass, stem diameter, number of stems, number of tillers, and the leaf contents of N, P, K, Ca, Mg and S were evaluated. The treatments did not produce significant differences in the biometric and yield parameters and in the leaf contents of macronutrients. The AGRI-001E hybrid of sweet sorghum showed an average of 4.7 m in height and stem diameter of 1.5 cm, with fresh and dry matter yields of 109.2 and 35.1 t ha-1 , respectively. The stalk production was 85.7 t ha-1 and was well above the minimum accepted by the sugarcane industries (50 t ha-1). The leaf contents of N, P, Ca and Mg were considered adequate. There was nutritional deficiency of K and S detected by chemical analysis of plant tissue, with no visible symptoms.
Urease inhibitor (NBPT) and the efficiency of urea applied in a single or split rates on yield of sweet sorghum
Keywords: Sorghum bicolor (L) Moench; Fertilizantes estabilizados; Adubação nitrogenada; Volatilização; Híbrido AGRI-001E; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO